2017
DOI: 10.5194/acp-2017-251
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CCN activity and organic hygroscopicity of aerosols downwind of an urban region in central Amazonia: Seasonal and diel variations and impact of anthropogenic emissions

Abstract: During the Observations and Modeling of the Green Ocean Amazon (GoAmazon2014/5) campaign, size-resolved cloud condensation nuclei (CCN) spectra were characterized at a research site (T3) 60 km downwind of the city of Manaus, Brazil, in central Amazonia for one year (12 March 2014 to 3 March 2015). Particle hygroscopicity (κCCN) and mixing state were derived from the size-resolved CCN spectra, and the hygroscopicity of the organic component of the aerosol (κorg) was then calculated from κCCN and concurrent chem… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
15
1
15

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(37 citation statements)
references
References 54 publications
6
15
1
15
Order By: Relevance
“…Whereas the variation of precursor molecule size and fragmentation during oxidation described above explain the general trend of increasing κ org with the oxidation level, laboratory 15 SOA generated from a wide range of precursors with different vapor pressures, molecular weights and structures, exhibit nearly the same relationship between κ org and O:C (Lambe et al, 2011). During the recent GoAmazon 2014/5 field campaign, κ org of various SOA components was derived and the variation of κ org with O:C also follows a similar relationship to that observed in laboratory studies (Thalman et al, 2017). While such a "universal" relationship allows 20 efficient parameterization of κ org based on O:C, it also raises a question why such a "universal" relationship is applicable to SOA generated from a range of precursors and under different conditions.…”
Section: A Model For Predicting the Dependence Of Effective Organic Hsupporting
confidence: 64%
See 2 more Smart Citations
“…Whereas the variation of precursor molecule size and fragmentation during oxidation described above explain the general trend of increasing κ org with the oxidation level, laboratory 15 SOA generated from a wide range of precursors with different vapor pressures, molecular weights and structures, exhibit nearly the same relationship between κ org and O:C (Lambe et al, 2011). During the recent GoAmazon 2014/5 field campaign, κ org of various SOA components was derived and the variation of κ org with O:C also follows a similar relationship to that observed in laboratory studies (Thalman et al, 2017). While such a "universal" relationship allows 20 efficient parameterization of κ org based on O:C, it also raises a question why such a "universal" relationship is applicable to SOA generated from a range of precursors and under different conditions.…”
Section: A Model For Predicting the Dependence Of Effective Organic Hsupporting
confidence: 64%
“…Despite the four orders of magnitude difference in C*, the derived variation of κ org with O:C falls within a relatively narrow band. Figure 5 also shows the linear relationship between κ org with O:C derived by Lambe et al (2011) for laboratory generated SOA with a wide range of O:C values, SOA hygroscopicity derived from 20 this study, and hygroscopicity of SOA factors derived from the measurements during recent GoAmazon 2014/5 campaign (Thalman et al, 2017). For β-caryophyllene SOA, κ org shown in Fig.…”
Section: A Model For Predicting the Dependence Of Effective Organic Hmentioning
confidence: 75%
See 1 more Smart Citation
“…Our AMS measurements (see Sect. 3.4.4) showed that the UT secondary organic aerosol (SOA) contains a substantial fraction of organics derived from the oxidation of isoprene (IEPOX-SOA) , which has relatively high hygroscopicity (κ ≥ 0.12) (Engelhart et al, 2011;Thalman et al, 2017). Assuming a conservative value of κ org ∼ = 0.1, which had been found previously for the Amazon PBL (Gunthe et al, 2009;Pöhlker et al, 2016), pure SOA particles would have to have diameters of ≥80 nm to act as CCN at 0.52 % supersaturation, whereas for pure ammonium sulfate particles (κ ∼ = 0.6), the critical diameter would be about 45 nm (Petters and Kreidenweis, 2007).…”
Section: Cloud Nucleating Propertiesmentioning
confidence: 99%
“…According to our observation, these particles are expected to show a significant hygroscopicity due to their secondary inorganic contents (Fuzzi et al, 2015), as well as the presence of organosulfates (Thalman et al, 2017). The light absorption of soot particles might be enhanced by mixing with non-absorbing species such as most of the organic compounds that can reflect the light to the soot part (Bond et al, 2013).…”
Section: Conclusion and Atmospheric Implicationsmentioning
confidence: 91%